Group-based funeral insurance in Ethiopia and Tanzania. - Dercon, S; Bold, T; Weerdt, J; Pankhurst, A (CSAE (University of Oxford), 2004)
A funeral is a costly occasion. This paper studies indigenous insurance institutions developed to cope with the high costs of funerals, based on evidence from rural areas in Tanzania and Ethiopia. These institutions are based on well-defined rules and regulations, often offering premium-based insurance for funeral expenses. Increasingly, they are also offering other forms of insurance and credit to cope with hardship. The paper argues that the characteristics and inclusiveness of these institutions make them well-placed as models to broaden insurance provision and other developmental activities in these communities. The history of these institutions is characterised by a resistance to attempts of political capture, and helps to understand their apparent resistance to engage more broadly with NGOs and government agencies. As a result, any attempt to expand their activities will have to be done cautiously.